2015
DOI: 10.1016/j.pmrj.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Are Elite Female Soccer Athletes at Risk for Disordered Eating Attitudes, Menstrual Dysfunction, and Stress Fractures?

Abstract: Elite female soccer athletes are susceptible to stress fractures and menstrual dysfunction and have delayed onset of menarche despite normal BMI and appropriate body perception and attitudes towards eating. Further studies are needed to better understand stress fracture risk in female soccer athletes and in other team sports to determine how these findings relate to long-term bone health in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 44 publications
3
32
1
2
Order By: Relevance
“…In a study with similar methods to ours, in terms of screening tools used, Izquierdo et al [26] reported similar rates of DE risk to the present study, finding that ~ 11% of male and female soccer players were at risk or were suffering from DE. In the only other study, to our knowledge, to assess the prevalence of DE risk in elite level soccer players, none of the 36 professional female soccer players taking part scored higher than the clinical cut-off of 20 on the EAT-26 [7]. By comparison, 8/70 of the female soccer players and 25/137 of the male soccer players reported scores ≥ 20 in the present study, which explains why the average EAT-26 scores in our study is much higher compared to their study (~ 10 vs. 3).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In a study with similar methods to ours, in terms of screening tools used, Izquierdo et al [26] reported similar rates of DE risk to the present study, finding that ~ 11% of male and female soccer players were at risk or were suffering from DE. In the only other study, to our knowledge, to assess the prevalence of DE risk in elite level soccer players, none of the 36 professional female soccer players taking part scored higher than the clinical cut-off of 20 on the EAT-26 [7]. By comparison, 8/70 of the female soccer players and 25/137 of the male soccer players reported scores ≥ 20 in the present study, which explains why the average EAT-26 scores in our study is much higher compared to their study (~ 10 vs. 3).…”
Section: Discussionmentioning
confidence: 77%
“…This is in contrast to the findings of Sundgot-Borgen [8], who found that the proportion of female soccer players with eating disorders was similar to a non-athlete control sample (24% vs. 23% of the cohort). Other studies in elite soccer players did not include a control group for comparison [7,26]. However, studies in other sports have also found DE risk to be similar or greater in female non-athletes than athletes [20,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elite youth athletes may be at-risk for poor nutrition and eating disorders 87. The German Young Olympic Athletes’ Lifestyle and Health Management Study collected data in 1,138 elite youth athletes with regard to eating disorders.…”
Section: Physical/physiological Risks For Injury In Elite Youth Athletesmentioning
confidence: 99%